(untitled) (Universal International Scientific Journal, 2026)
This scientific article provides a comprehensive analysis of the importance of scientific research and pedagogical innovations in the education system, modern teaching methods, digital educational technologies, and scientific and pedagogical approaches. It also highlights the reforms being implemented in the field of education in the conditions of New Uzbekistan, their scientific foundations and practical results. The article identifies existing problems and puts forward specific proposals and solutions aimed at eliminating them.